A family of vector bundles on P3 of homological dimension 2 and X (EndE) = 1 - Soares, H.; Miró-Roig, M.; Mendes, S. (Matemática Contemporânea, 2020)
For any odd integer ? ≤ −5, we construct a family of rank 3 vector bundles E? on P3 with minimal linear resolution and satisfying ? (End E? ) = 1.